Contracting out by local governments in transitioning nations: the role of technical assistance in Ukraine - Brown, Trevor L. (2001)
This article examines the factors that promote and inhibit contracting out by local governments in transitioning nations. Specifically, this article analyzes the effect of a variety of factors on the decision by Ukrainian local governments to contract out public services. The article uses Logit techniques to analyze the results of a 72-city survey undertaken in Ukraine in 1997 and 1998. Analysis of the data indicates that the presence of a technical assistance program in particular increases the likelihood that a local government will engage in contracting out. The findings also demonstrate the importance of factors identified by contracting out models of local governments in advanced industrialized contexts. - Reproduced
Keywords: Technical cooperation - Ukraiane; Local government - Ukraine; Local government